1988
DOI: 10.1007/bf01907104
|View full text |Cite
|
Sign up to set email alerts
|

Right heart catheterization in rats with pulmonary hypertension and right ventricular hypertrophy

Abstract: Using a special Millar ultraminiature catheter pressure transducer, right ventricular functional parameters were measured in anesthetized, closed-chest rats under control conditions, during acute pulmonary hypertension and after induction of right ventricular hypertrophy. Acute i.v. infusion of noradrenaline and a brief period of hypoxia in female Sprague-Dawley rats elicited a marked increase in right ventricular systolic pressure (RVSP) and in the maximal rate of rise in right ventricular pressure (RV dp/dtm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Also, RVSP was elevated in this rat strain, although not to the same extent as previously observed in SpragueDawley rats (24). The stimulation intervals with NE, however, were longer in most of the studies in which NE had been shown to elevate RVSP (1,8).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Also, RVSP was elevated in this rat strain, although not to the same extent as previously observed in SpragueDawley rats (24). The stimulation intervals with NE, however, were longer in most of the studies in which NE had been shown to elevate RVSP (1,8).…”
Section: Discussionsupporting
confidence: 58%
“…The catheter must be directed from the jugular vein and the right atrium into the right ventricle, a procedure that was established previously (24). When the catheter is placed in the right ventricle, the catheter tip has to follow the blood stream, i.e., a diversion from the direction of inflow, that ultimately passes the pulmonary valve in an antegrade fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At HT we~ (9) creased, although heart rate was not changed compared with the control value. T3 treatment supports the predominance of the fast V, isomyosin in the rat.…”
Section: Hemodynamic and Functional Alterationsmentioning
confidence: 72%
“…A soft catheter linked to a pressure transducer was inserted into the right ventricle through the right external jugular vein. Right ventricle systolic pressure (RVSP), approximately equal to pulmonary arterial pressure,31, 32 was recorded on the monitor of the Powerlab system (AD Instruments, Castle Hill, New South Wales, Australia). Systemic systolic pressure was measured through a catheter inserted into the carotid artery.…”
Section: Methodsmentioning
confidence: 99%